2021
DOI: 10.1038/s41598-021-85798-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between oxygen changes in the brain and periphery following physiological activation and the actions of heroin and cocaine

Abstract: Using two-sensor electrochemical recordings in freely moving rats, we examined the relationship between physiological and drug-induced oxygen fluctuations in the brain and periphery. Animals chronically implanted with oxygen sensors in the nucleus accumbens (NAc) and subcutaneous (SC) space were subjected to several mildly arousing stimuli (sound, tail-pinch and social interaction) and intravenous injections of cocaine and heroin. Arousing stimuli induced rapid increases in NAc oxygen levels followed by and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…This comparison revealed that both tail-pinch and social interaction induced rapid oxygen increases, similar in their time-course in the NAc and SNr [28] (Fig. 6, Ref.…”
Section: Neural Activation and Peripheral Vasoconstriction As The Factors Determining Intra-brain Fluctuations In Oxygen And Glucosementioning
confidence: 64%
See 4 more Smart Citations
“…This comparison revealed that both tail-pinch and social interaction induced rapid oxygen increases, similar in their time-course in the NAc and SNr [28] (Fig. 6, Ref.…”
Section: Neural Activation and Peripheral Vasoconstriction As The Factors Determining Intra-brain Fluctuations In Oxygen And Glucosementioning
confidence: 64%
“…5, Ref. [28]). Moreover, these changes are very tightly correlated (r = -0.76 and -0.92 for tail-pinch and social interaction, respectively).…”
Section: Neural Activation and Peripheral Vasoconstriction As The Factors Determining Intra-brain Fluctuations In Oxygen And Glucosementioning
confidence: 99%
See 3 more Smart Citations